The design and physical characterization of a multileaf collimator for robotic radiosurgery. (10th February 2016) - Asmerom, G; Bourne, D; Chappelow, J; Goggin, L M; Heitz, R; Jordan, P; Kilby, W; Laing, T; Maurer, C R; Noll, J M; Sayeh, S; Weber, A
Abstract: A multileaf collimator (MLC) optimized for SBRT delivery with the CyberKnife ® Robotic Radiosurgery System (Accuray Incorporated, Sunnyvale, CA, USA) is described. The MLC is exchangeable with the alternate fixed and variable circular aperture collimator systems. The non-coplanar workspace is effectively equivalent for all three collimation types. The same range of tracking options, including real-time respiratory motion tracking, and the same tolerance on beam pointing accuracy (≤0.95 mm) is maintained with all three collimation types. The MLC includes 52 flat-sided leaves, each of which is 90 mm tall and projects 3.85 mm width at the nominal treatment distance of 800 mm SAD. The design allows 100% overtravel and unrestricted interdigitation. Leaf position is determined by primary motor encoders and is checked with a secondary optical camera system. Maximum leakage, including inter-leaf and under the closed position leaf-tip gap was measured on five units to be ≤0.44%, while mean leakage and transmission ranged from 0.22%–0.25%. Leaf positioning accuracy measured over the full range of leaf positions, all robot and MLC orientations, and including variation with leaf motion direction and accumulated leaf motion after initialization had a mean error <0.2 mm, with 2%–98% range of ≤±0.5 mm (projected at 800 mm SAD) on three units tested. The only factor found to effect leaf positioning accuracy was sag under gravity, which systematically altered leaf positions by 0.1 mm. Tilting the leaves to reduce inter-leaf leakage results in 0.5 mm asymmetry in leaf-side penumbra at 100 mm depth, and a partial leaf-edge transmission pattern analogous to the tongue and groove effect observed with interlocking leaves.